2017
DOI: 10.1128/jvi.01085-16
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Marburg Virus VP35 Oligomerization Domain

Abstract: Marburg virus (MARV) is a highly pathogenic filovirus that is classified in a genus distinct from that of Ebola virus (EBOV) (genera Marburgvirus and Ebolavirus, respectively). Both viruses produce a multifunctional protein termed VP35, which acts as a polymerase cofactor, a viral protein chaperone, and an antagonist of the innate immune response. VP35 contains a central oligomerization domain with a predicted coiled-coil motif. This domain has been shown to be essential for RNA polymerase function. Here we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 50 publications
(70 reference statements)
3
59
1
Order By: Relevance
“…P is the most variable protein and shares the lowest sequence identities among NNS RNA viruses. Strikingly, despite the low sequence conservation, all P (or VP35 in Filoviridae) share a common feature and exist as an oligomer (dimer, trimer, or tetramer) in solution [53][54][55][56][57][58][59][60] ( Fig. 3g and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P is the most variable protein and shares the lowest sequence identities among NNS RNA viruses. Strikingly, despite the low sequence conservation, all P (or VP35 in Filoviridae) share a common feature and exist as an oligomer (dimer, trimer, or tetramer) in solution [53][54][55][56][57][58][59][60] ( Fig. 3g and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further investigations are required to discover whether the RSV L alone exhibits the same way as VSV L. Interestingly, all RNA polymerases of NNS RNA viruses require P (or VP35 in Filoviridae), but P exists as diverse oligomeric protein ( Supplementary Fig. 9) and shares low sequence identity [53][54][55][56][57][58][59][60] . In most cases, the protomers, the basic building blocks of oligomeric proteins, assemble into a higher-order oligomer following a defined repeating or symmetry rule.…”
Section: Discussionmentioning
confidence: 99%
“…A co-immunoprecipitation assay demonstrated that FLAG-tagged batVP35 can co-precipitate with hemagglutinin (HA)-tagged batVP35, consistent with oligomerization (Figure 6A). Both eVP35 and mVP35 form tetramers, as demonstrated by light scattering analyses, although work has described the crystal structure of the N terminus of mVP35 forming a trimer instead (Bruhn et al, 2017; Edwards et al, 2016). To determine the oligomeric state of batVP35, we used multi-angle light scattering coupled to size exclusion chromatography and found that it also forms a tetramer (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Multi-pass TEM simulations. In the following we show multi-pass TEM simulations of three model systems of known structure: graphene 33,34 , the hexameric unit of the immature HIV-1 Gag CTD-SP1 lattice (HIV-1 Gag, PDB ID: 5I4T) 35 , and the Marburg Virus 7 VP35 Oligomerization Domain P4222 (MARV VP35, PDB ID: 5TOI) 36 . In the simulations (see methods for details) an electron wave passes through the sample of an aberration-free multi-pass TEM multiple times.…”
Section: Resultsmentioning
confidence: 99%